A New Insight of Talang Akar Formation in the Ridho Field, North Palembang Sub-basin, Indonesia: An Integrated Approach - Togi Y. Sitinjak; Ricky A. Tampubolon; Ardian Pratama; Wildanto P. Nusantara; Aziza Muis; Harsanti Setiani (Berita Sedimentologi, 2020)
The synrift sandstone deposits of Eo-Oligocene Lemat (LMF) and Oligo-Miocene Talang Akar Formations (TAF) are the most well -known hydrocarbon reservoirs in the South Sumatra Basin, Indonesia. However, only limited studies on TAF in the North Palembang Sub-Basin have been published. In the Ridho field, TAF is characterized by fining-up sequences of inter bedded, fine to medium-grained sandstones and shales overlain by a coal layer as the top marker, while LMF comprises of continuous blocky-shaped, medium to coarse-grained, conglomeratic sandstones.Previous lithostratigraphy-driven sand to sand correlation between wells has created difficulties in understanding the geology and in producing consistent correlation, especially within the TAF. In order to define chronostratigraphy-based correlation and interpret the depositional environment of TAF and LMF, an integration between palynological, core study and petrophysical analysis was performed. The result of this integrated approach demonstrates aligned hypotheses. The occurrence of pollen Meyeripollis naharkotensis and Florschuetzia trilobata along the studied wells suggest Late Oligocene age. The palynology study subdivides TAF into three backmangrove-intertidal sand units with an increase of marine influence defining a transgression to the top of the TAF. The transgressive event is identified in core sample by lesser tidal influx sedimentary structures such as ripple, mudlayer, flaser and also finer grained sandstone at the top of TAF. Furthermore, based on petrophysical evaluation, better sand quality with lower NTG (net -to gross) near top TAF confirms the retrogradational event in this formation.The new sand unit definitions from the current study provide more consistent correlation in terms of sand thickness and characteristics for future modeling purposes.